Functionality of spray-dried strawberry powder: effects of whey protein isolate and maltodextrin. Issue 1 (1st January 2018) - Gong, Zhiqing; Yu, Manman; Wang, Wenliang; Shi, Xianquan
ABSTRACT: The effectiveness of two drying agents, namely whey protein isolate (WPI) and maltodextrin (MD), was evaluated during spray-drying of strawberry puree. With the increase of WPI substitution in the feed material, the surface tension of strawberry puree decreased, and powder recovery increased. Powder recovery (Rp ) increased from 39.2 ± 2.3% (S:MD:WPI = 60:40:0) to 56.5 ± 2.8% when MD was replaced by WPI (S:MD:WPI = 60:39:1). Surface morphology of powders showed that the addition of WPI resulted in shrunken particle surface, which gave rise to smaller DB and particle size. The particles were not spherical, and even with the addition of 0.5% WPI, the particle morphology was altered. The surface shrinkage of strawberry powder increased with increase in WPI from 0.5% to 10%. The production efficiency of strawberry powder could be greatly improved when MD was replaced by 1% WPI.